The Role of Mentoring Program in Enhancing Mentees’ Academic Performance - Azman Ismail; Michael Kho Khian Jui (Journal of Education and Learning (EduLearn), 2014)
According to institutions of higher learning literature, mentoring program has two important features: communication and support. The ability of mentors to appropriately implement comfortable communication and provide adequate support may ehance positive mentee outcomes, especially academic performance. Although the nature of this relationship is crucial, little is known about the role of mentoring program as an important predictor of mentees’ academic performance in the higher education mentoring research literature. Therefore, this study was conducted to measure the relationship between mentoring program and mentees’ academic performance using self-administered questionnaires gathered from undergraduate students in Malaysian institutions of higher learning in Sarawak. The results of SmartPLS path model showed two important outcomes: firstly, communication positively and significantly correlated with academic performance. Secondly, support positively and significantly correlated with academic performance. The result demonstrates that mentoring program does act as an important predictor of mentees’ academic performance in the organizational sample. Thus, discussion, implications and conclusion are elaborated.